Joseph Barlow Felt Osgood, The Charter and Ordinances of the City of Salem, Together with the Acts of the Legislature Relating to the City: Collated and Revised Pursuant to an Order of the City Council 67 (1853) - (:unkn) unknown (My University, 1847)
§ 18: No gun-cotton, or other substance prepared, like it, for explosion, shall be kept within the limits of such town or city, excepting under the regulations and penalties that were then applicable by law to gunpowder; and if it shall be considered necessary for public safety, they may restrict the quantity to be so kept to one-fifth of the weight of gunpowder allowed by law in each case provided for.
Keywords: GUNPOWDER - STORAGE